Learning about the unknown Spitzenkandidaten: The role of media exposure during the 2019 European Parliament elections. (June 2022) - Richter, Simon; Stier, Sebastian
The Spitzenkandidaten were meant to personalize European Parliament elections. This paper asks whether and through which channels the lead candidates were actually able to make themselves known among voters – a necessary precondition for any electoral effect. Combining panel surveys and online tracking data, the study explores candidate learning during the German 2019 European Parliament election campaign and relates learning to different types of news exposure, with a special focus on online news. The results show that learning was limited and unevenly distributed across candidates. However exposure to candidate-specific online news and most types of offline news helped to acquire knowledge. The findings imply that Spitzenkandidaten stick to voters' minds when they get exposed to them, but that exposure is infrequent in high-choice media environments.